Komponen Pendorong Performa Belajar Mahasiswa - Ranjani Nurfatimah; Christian Wirandedi Wolor; Marsofiyati Marsofiyati (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2023)
This study was conducted to examine the influence of Discipline (X1), Motivation (X2) and Student Competence (X3) on Learning Achievement (Y). This study uses a quantitative method with a sample size of 100 respondents, where the respondents were students at the Jakarta State University with an age range of 19-22 years. Data was collected online by distributing questionnaires/statements using Microsoft Form assistance which were measured using Likert scale options from 1 to 5. The data analysis technique used was SmartPLS (Partial Least Square) Statistical software version 4.0.9.2. The results showed that: 1) Discipline has a positive and significant effect on learning achievement. 2) Motivation has a positive and significant effect on learning achievement. 3) Student competence has a positive and significant effect on learning achievement. 4) Discipline, motivation and student competence positively and significantly affect learning achievement. This is by the formulation of the problem, namely discipline, motivation and student competence simultaneously affect learning achievement.